Comparison of Dynamic Headspace Trapping on Tenax TA and Headspace Stir Bar Sorptive Extraction for Analysis of Grilled Chicken (Yakitori) Volatiles - Ngamchuachit, Panita; Kitai, Yurika; Keeratipibul, Suwimon; Phuwapraisirisan, Preecha (Applied Science and Engineering Progress, 2020)
Two headspace extractions, dynamic headspace trapping on Tenax TA (DHS-Tenax TA) and headspace stir bar sorptive extraction (SBSE), were performed to compare the volatile profile in Japanese commercially processed grilled chicken produced in two processing steps: after dipping in thin sauce and then grilling (S1) and S1 after dipping in thick sauce (S2). Eighty-two volatile compounds were identified. Although DHS-Tenax TA extracted a larger number and higher amounts of volatile compounds for MS than SBSE, SBSE detected more aromas at the olfactometer than DHS-Tenax. Lipid oxidation products (aldehydes, alcohols, ketone, and phenols) and Maillard reaction products (Strecker aldehydes, nitrogen- and sulfur-containing compounds, furan(one)s, and pyrrole) are major compounds. DHS-Tenax TA was more suitable for the detection of volatile compounds from the Maillard and Strecker degradation products, such as pyrazines and furan(one)s, whereas SBSE was adequate for hydrocarbons and terpenes, and aroma compounds that were not detected by MS. Furan(one)s were only identified in S2 samples due to the presence of sugars in the thick sauce.